Young Coconut Juice Reduces Some Histopathological Changes Associated with Alzheimer's Disease through the Modulation of Estrogen Receptors in Orchidectomized Rat Brains. (29th November 2019) - Balit, Tatcha; Abdel-Wahhab, Mosaad A.; Radenahmad, Nisaudah
Abstract : Propos e. This study aimed to evaluate the protective role of young coconut juice (YCJ) against the pathological changes in Alzheimer's disease (AD) in orchidectomized (orx) rats. Methods and Results . Animals were divided into 7 groups including: baseline normal control group, sham control, orx rat group, orx rat group injected with 2.5  μ g/kg b.w. estradiol benzoate (EB) 3 days a week for 10 weeks, and the orx rat groups treated orally with 10, 20, and 40 ml/kg b.w. of YCJ for 10 weeks. At the end of treatment period, animals were sacrificed and the brain of each rat was removed, fixed in 10% neutral formalin, and stained by specific antibodies against NF200, parvalbumin (PV), β -amyloid (A β ), and estrogen receptors (ER α and ER β ). The results showed that the number of NF200- and PV-reactive neurons in the hippocampus and cerebral cortex was significantly reduced in orx rats. However, it restored to normal in orx rats injected with EB or those administrated with YCJ in a dose-related manner. Neurons containing β -amyloid (A β ), a hallmark of Alzheimer's disease (AD), were found to be increased in the orx rats; however; they were reduced by EB injection or YCJ administration. These results suggested the binding of the YCJ active ingredient(s) with estrogen receptors (ERs) in the brain as indicated by the detection of ER α and ER β in neurons since a significant correlation was detected between NF200-/PV-reactive neurons vs ER α -/ER β -reactive neurons. Conclusion . It could be concluded that YCJ is effective as EB in reducing AD pathology, probably by being selective estrogen receptor modulators.